Theoretical Refinements to the Heliospheric Upwind eXtrapolation Technique and Application to in-situ Measurements - Issan , Opal; Riley, Pete (Frontiers in Astronomy and Space Sciences, 2022)
The large-scale structure and evolution of the solar wind are typically reproduced with reasonable fidelity using three-dimensional magnetohydrodynamic (MHD) models. However, such models are difficult to implement by the scientific community in general, because they require technical expertise and significant computational resources. Previously, we demonstrated how a simplified two-dimensional surrogate solar wind model, the Heliospheric Upwind eXtrapolation (HUX) technique, could reconstruct MHD solutions in the ecliptic plane, given either an inner (or outer) radial boundary condition. Here, we further develop the HUX technique and apply it to a range of solar wind in-situ datasets. Specifically, we: (1) provide a thorough mathematical analysis of the underlying reduced momentum equation describing the solar wind. (2) Propose flux-limiter numerical schemes that more accurately capture stream interaction regions and rarefaction regions; and (3) Apply the HUX technique to a variety of in-situ spacecraft measurements, focusing on Helios (1 and 2) and near-Earth spacecraft (Wind/ACE), for which near-latitudinal alignments occurred. We suggest that this refined HUX tool can be used for both retrospective studies as well as real-time predictions to better understand and forecast the large-scale structure and origin of the solar wind.